2014
DOI: 10.1016/s1473-3099(14)70710-8
|View full text |Cite
|
Sign up to set email alerts
|

Infection-induced inflammation and cerebral injury in preterm infants

Abstract: Summary Preterm birth and infectious diseases are the most common causes of neonatal and early childhood deaths worldwide. The rates of preterm birth have increased over recent decades and currently account for 11% of all births globally. Preterm infants are at significant risk of severe infection in early life and throughout childhood. Bacteraemia and/or inflammation during the neonatal period in preterm infants is associated with adverse outcomes, including death, chronic lung disease and neurodevelopmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
219
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 242 publications
(242 citation statements)
references
References 146 publications
(142 reference statements)
3
219
0
7
Order By: Relevance
“…High circulating levels of inflammatory cytokines have been observed in very preterm infants exposed to intensive care (11) and have been repeatedly linked to worse outcomes such as bronchopulmonary dysplasia (12), white matter injury, and neurodevelopmental impairments (16). These results have led to speculations that the innate immune system of these infants is hyper-rather than hypo-responsive during the neonatal period (17).…”
Section: Discussionmentioning
confidence: 99%
“…High circulating levels of inflammatory cytokines have been observed in very preterm infants exposed to intensive care (11) and have been repeatedly linked to worse outcomes such as bronchopulmonary dysplasia (12), white matter injury, and neurodevelopmental impairments (16). These results have led to speculations that the innate immune system of these infants is hyper-rather than hypo-responsive during the neonatal period (17).…”
Section: Discussionmentioning
confidence: 99%
“…Prompted by the growing epidemiologic and clinical evidence that bacteremia in human newborns, even in the absence of positive CSF cultures, is associated with subsequent CNS injury [2][3][4][5]30, 31], we tested the hypothesis that S. epidermidis bacteremia can induce brain injury and we characterized the potential roles of TLR2 in this process. To this end, we used an established neonatal S. epidermidis sepsis model [20] to demonstrate for the first time that (1) S. epidermidis bacteremia, in the absence of viable bacteria in the CSF, has a detrimental impact on the development of the neonatal brain via both rapid TLR2-dependent caspase-3 activation, as well as longer-term TLR2-independent pathways, culminating in reduced white and gray matter volumes; and (2) neonatal TLR2 is functional in host defense against S. epidermidis and serves to accelerate bacterial clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm birth is associated with a high risk of brain injury that can contribute to neurological disorders such as cerebral palsy, autism, and possibly schizophrenia [1,2]. Cerebral white-matter injury is the most common form of injury to the preterm brain and is associated with a high risk of neurodevelopmental impairment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Keywords: astrocyte; gap junction; Cx43; neonatal sepsis demonstrated that neonatal sepsis directly causes brain damage such as white matter lesions and periventricular leukomalacia, and is closely associated with a high rate of lethality in neonates [3] . Furthermore, survivors of neonatal sepsis often show severe long-term cognitive impairment and adverse neurologic outcomes [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%